Aphid alarm pheromone mimicry in transgenic Chrysanthemum morifolium: insights into the potential of (E)-β-farnesene for aphid resistance - Li, Jinjin; Hu, Hao; Ren, Shengjing; Yu, Lu; Luo, Yuanyuan; Li, Jiawen; Zeng, Tuo; Wang, Manqun; Wang, Caiyun (Frontiers in Plant Science, 2024)
(E)-β-Farnesene (EBF) serves as the primary component of the alarm pheromone used by most aphid pest species. Pyrethrum (Tanacetum cinerariifolium) exhibits tissue-specific regulation of EBF accumulation and release, effectively mimicking the aphid alarm signal, deterring aphid attacks while attracting aphid predators. However, cultivated chrysanthemum (Chrysanthemum morifolium), a popular and economically significant flower, is highly vulnerable to aphid infestations. In this study, we investigated the high expression of the pyrethrum EBF synthase (TcEbFS) gene promoter in the flower head and stem, particularly in the parenchyma cells. Subsequently, we introduced the TcEbFS gene, under the control of its native promoter, into cultivated chrysanthemum. This genetic modification led to increased EBF accumulation in the flower stem and young flower bud, which are the most susceptible tissues to aphid attacks. Analysis revealed that aphids feeding on transgenic chrysanthemum exhibited prolonged probing times and extended salivation durations during the phloem phase, indicating that EBF in the cortex cells hindered their host-location behavior. Interestingly, the heightened emission of EBF was only observed in transgenic chrysanthemum flowers after mechanical damage. Furthermore, we explored the potential of this transgenic chrysanthemum for aphid resistance by comparing the spatial distribution and storage of terpene volatiles in different organs and tissues of pyrethrum and chrysanthemum. This study provides valuable insights into future trials aiming for a more accurate replication of alarm pheromone release in plants. It highlights the complexities of utilizing EBF for aphid resistance in cultivated chrysanthemum and calls for further investigations to enhance our understanding of this defense mechanism.